Company Size, Profitability, Leverage, and Institutional Ownership: Their Influence on Tax Avoidance with Financial Performance as a Moderating Variable in Indonesia's Construction Sector (2018-2022) - Nursandhi, Budi; Novatiani, Ait; Irwansyah, Irwansyah (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2025)
The purpose of this study is to determine and analyze the influence of company size, profitability, leverage, and institutional ownership on tax avoidance, with financial performance as a moderating variable in construction industry companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The research employs a quantitative approach, utilizing secondary data from annual reports of these companies. The study finds that firm size, profitability, and leverage significantly affect tax avoidance, while institutional ownership does not show a significant impact. Furthermore, financial performance is shown to moderate the relationship between these variables and tax avoidance. The findings contribute to the understanding of tax avoidance behaviors in the Indonesian construction sector and provide insights for regulators to improve tax compliance. The study underscores the importance of financial performance as a moderating variable and its role in tax planning strategies.